V avguste 44-go . In August 1944 - Ptashuk, Mikhail (Belarusfilm, 2002)
Duration: 01:56:00 Crime drama set in the last days of war, in 1944. Tthe SMERSH agents feature as 'good guys' fighting against Nazi collaborators.